2011
DOI: 10.1159/000324673
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies on the Prevention of the Ovalbumin-Induced Allergic Response by <i>Enterococcus faecalis</i> CECT7121 in Mice

Abstract: Background: Allergic diseases are featured by an increased production of IgE due to an imbalance in the immune response towards a Th2 profile. In this work, the ability of Enterococcus faecalis CECT7121 to regulate this Th2-exaggerated response in a murine model of ovalbumin (OVA)-induced allergy was studied. Methods: BALB/c mice intragastrically inoculated with E. faecalis CECT7121 before and during a subcutaneous immunization protocol with OVA were studied in comparison with an immunized control group. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…This probiotic also decreased the proliferation of splenocytes and the secretion of Th2 cytokines [23]. In the latter model, we have demonstrated that the previous implantation of E. faecalis CECT7121 in the intestinal mucosa prevents the development of the allergic status.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…This probiotic also decreased the proliferation of splenocytes and the secretion of Th2 cytokines [23]. In the latter model, we have demonstrated that the previous implantation of E. faecalis CECT7121 in the intestinal mucosa prevents the development of the allergic status.…”
Section: Introductionmentioning
confidence: 63%
“…Previously, our group has demonstrated that the i.g. administration of Enterococcus faecalis CECT7121, prior to the sensitization induced by the administration of OVA, can prevent the establishment of the allergic response [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations